2017
DOI: 10.1186/s12879-017-2475-9
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden and antimicrobial resistance of invasive group B streptococcus among infants in China: a protocol for a national prospective observational study

Abstract: BackgroundGroup B Streptococcus (GBS) is a cause of neonatal sepsis, pneumonia, and meningitis that can lead to neurological sequelae in infants less than 3 months of age. The GBS disease burden is not known in China, therefore it cannot receive major attention. The main objectives of this study are the evaluation of the incidence of neonatal GBS infection, GBS case-fatality ratio, its serotypes and genotypes, bacterial resistance, clinical treatment and outcomes in China.MethodsWe are conducting a nation-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Participating hospitals met the following inclusion criteria ( 8 ): large, urban, tertiary-care center; adequate research capabilities and facilities to conduct the study, including laboratory facilities and the ability to identify, process, and store GBS isolates; investigators willing to devote time to the study; and location, to ensure > 1 hospital from each region. Trained site investigators in each participating hospital collected clinical data by using a standardized case report form.…”
Section: Methodsmentioning
confidence: 99%
“…Participating hospitals met the following inclusion criteria ( 8 ): large, urban, tertiary-care center; adequate research capabilities and facilities to conduct the study, including laboratory facilities and the ability to identify, process, and store GBS isolates; investigators willing to devote time to the study; and location, to ensure > 1 hospital from each region. Trained site investigators in each participating hospital collected clinical data by using a standardized case report form.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to structure-activity relationship (SAR) studies, we found that HMOs potentiate the activity of select intracellular targeting antibiotics (32). This included three antibiotics to which GBS has evolved resistance, aminoglycosides, macrolides, and tetracyclines (33)(34)(35)(36)(37)(38)(39)(40)(41)(42). At their 50% inhibitory concentration (IC 50 ), HMO extracts reduced the MICs of certain intracellular targeting antibiotics up to 32-fold (Table 1).…”
mentioning
confidence: 96%
“…Severe inflammation and MODS greatly threat patients' life. The increasing prevalence of drug resistant compels us to find new and effective approaches for the diagnosis and therapy of severe inflammation [26]. MicroRNAs such as miR-9 have been reported to be involved in inflammation and to play an important role in preventing inflammation developing to MODS, while the specific mechanism is still unclear [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%